Penerapan Strategi Directed Reading Thinking Activity (DRTA) untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas V SDN 066050 Medan - Juliana Juliana; Meikardo Samuel Prayuda; Darinda Sofia Tanjung (Journal on Education, 2023)
The backgrounds of carrying out this research are: 1) the students find it difficult to comprehend reading materials; 2) the students’ learning results are low or less than Mastery Minimum Criteria; 3) the teaching strategy used by the teacher is inappropriate in teaching reading comprehension to the students. The objective of this research is to prove that the implementation of Directed Reading Thinking Activity (henceforth, DRTA) strategy is effective to enhance reading comprehension of the fifth grade students of SD Negeri 066050 Medan. This is Classroom Action Research (henceforth, CAR). The sample of this CAR are the fifth grade students of SD Negeri 066050 Medan consisting of 25 students. The students’ learning results in the pre-cycle or pre-test is still categorized unsatisfactory (very low). The students’ mean score in the pre-cycle or pre-test is 56.80 (24%). After completing cycle one, the students’ mean score increased into 66.20 (40%). After doing reflection and finishing cycle two, it was found out that the students’ mean score increased into 77.28 (80%). It is concluded that the application of DRTA strategy is able to improve reading comprehension of the fifth grade students of SD Negeri 066050 Medan.